PSYCHOLOGICAL FIRST AID TO REDUCE TRAUMA AND DEPRESSION IN THE VICTIMS OF SEXUAL ABUSE: LITERATURE REVIEW - Rosyida, Naila Zulfa; Sari, Jayanti Dian Eka; Fatah, Mohammad Zainal (Journal of Community Mental Health and Public Policy, 2024)
Background: The most concerning now is the increasing cases of sexual abuse. The impact of sexual abuse is very detrimental, victims will experience a decrease in appetite, stress, trauma, and even depression. Purpose: To find out the description of Psychological First Aid (PFA) for victims of sexual abuse. Method: This is narrative literature review. The inclusion criteria used were the year of publication between 2019-2023, free full text, English or Indonesian, research subjects were victims of sexual abuse, victims' families, and psychology. The data searching method used was the Boolean searching method with the keywords "PFA" AND "sexual abuse" AND "trauma" OR "depression". Selection of articles were based on the prism method with data sources from Google Scholar. Results: PFA plays an important role in the long-term effects of sexual abuse in the form of trauma and depression. PFA can be done by providing modules, psychoeducation, counseling, and coaching to victims of sexual abuse. Therefore, both families and psychologists must work together in conducting PFA so that victims do not experience trauma and depression due to sexual abuse. Conclusion: There is an influence on the provision of PFA in reducing trauma and depression in victims of sexual abuse. Abstrak Latar Belakang: Hal yang paling memprihatinkan saat ini adalah meningkatnya kasus sexual abuse. Dampak sexual abuse sangat merugikan, korban akan mengalami penurunan nafsu makan, stress, trauma bahkan depresi. Tujuan: Untuk mengetahui gambaran Psychological First Aid (PFA) bagi korban sexual abuse. Metode: Ini adalah narrative literatur review. Kriteria inklusi yang digunakan adalah tahun terbit 2019-2023, free full text, bahasa Inggris atau bahasa Indonesia, subjek penelitian adalah korban sexual abuse, keluarga korban dan Psikologi. Pencarian data menggunakan metode boolean searching dengan kata kunci “PFA“DAN“sexual abuse” DAN “trauma” ATAU “depresi”. Pemilihan artikel berdasarkan metode prisma dengan sumber data dari google scholar. Hasil: PFA berperan penting terhadap dampak jangka panjang dari sexual abuse berupa trauma dan depresi. PFA dapat dilakukan dengan memberikan modul, psikoedukasi, konseling dan pembinaan pada korban sexual abuse. Oleh karena itu, baik keluarga maupun ahli psikologi harus bekerja sama dalam melakukan PFA agar korban tidak mengalami trauma dan depresi akibat sexual abuse. Kesimpulan: Terdapat pengaruh terhadap pemberian PFA pada penurunan trauma dan depresi pada korban sexual abuse.